2013
DOI: 10.2320/matertrans.m2013047
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Oxygen Content by Varying Oxygen Partial Pressure in Chromium Oxynitride Thin Films Prepared by Pulsed Laser Deposition

Abstract: Chromium oxynitride Cr(N,O) thin films were prepared by pulsed laser deposition in a highly reactive atmosphere, which consisted of pure oxygen gas and nitrogen plasma from a radio-frequency radical source. In order to control the oxygen content in the thin films, oxygen partial pressure (P O2 ) in the chamber was varied from 5 to 10 © 10 ¹5 Pa under a fixed total pressure of 1.5 © 10 ¹2 Pa. The thin films were then characterized by X-ray diffraction, infrared spectroscopy, electron energy loss spectroscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…For controlling the oxygen content, we adopted a method of varying the oxygen partial pressure in the deposition atmosphere, as reported in a previous paper. 10) Figure 1 shows a schematic image of PLD apparatus used for preparing the thin films. An ablation plasma was produced by irradiating a Nd: yttrium aluminum garnet laser (355 nm) onto a Cr target (99.9% purity).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For controlling the oxygen content, we adopted a method of varying the oxygen partial pressure in the deposition atmosphere, as reported in a previous paper. 10) Figure 1 shows a schematic image of PLD apparatus used for preparing the thin films. An ablation plasma was produced by irradiating a Nd: yttrium aluminum garnet laser (355 nm) onto a Cr target (99.9% purity).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous result showed that the lattice constant of Cr(N,O) decreased with increasing oxygen content. 10) Hence, this shift indicates an increase in the oxygen content of the thin film or stress relaxation due to the heat treatment. Figure 7 shows the BFIs and ED patterns of sample M before the oxidation test (left) and after the oxidation test at 1073 K, which is the highest temperature maintaining the B1 structure (right).…”
Section: Phase Identification and Microstructure Observationmentioning
confidence: 99%
“…We expected that B1-CrO would have a high hardness because of our previous results involving chromium oxynitride Cr(N,O) thin films. [11][12][13][14] Cr(N,O) thin films, which can be considered as a solid solution of B1-CrO and B1-CrN, were synthesized by pulsed laser deposition (PLD). Oxygen atoms were dissolved in CrN to 37 mol.…”
mentioning
confidence: 99%
“…%, and the hardness of the resulting Cr(N,O) thin films increased from the 18 GPa of CrN up to 32 GPa with increasing oxygen content. 13 By extrapolating the hardness versus composition plot, it was expected that the hardness of B1-CrO would exceed 40 GPa, a very high value for an oxide.…”
mentioning
confidence: 99%
See 1 more Smart Citation